1998
DOI: 10.1046/j.1471-4159.1998.71020732.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Na,K‐ATPase Isoenzymes in the Rat Diabetic Neuropathy: Protective Effect of Dietary Supplementation with n‐3 Fatty Acids

Abstract: Diabetic neuropathy is a degenerative complication of diabetes accompanied by an alteration of nerve conduction velocity (NCV) and Na,K-ATPase activity. The present study in rats was designed first to measure diabetes-induced abnormalities in Na,K-ATPase activity, isoenzyme expression, fatty acid content in sciatic nerve membranes, and NOV and second to assess the preventive ability of a fish oil-rich diet (rich in n-3 fatty acids) on these abnormalities. Diabetes was induced by intravenous streptozotocin inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 32 publications
3
33
2
Order By: Relevance
“…Hence, Na + -K + ATPase activity is central to phototransduction and any perturbation in its activity will manifest as an altered phototransduction amplitude [28]. It is noteworthy that in diabetes, reduced Na + -K + ATPase activity is observed in a variety of different cell types [29], including those of the retina [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, Na + -K + ATPase activity is central to phototransduction and any perturbation in its activity will manifest as an altered phototransduction amplitude [28]. It is noteworthy that in diabetes, reduced Na + -K + ATPase activity is observed in a variety of different cell types [29], including those of the retina [16].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of Na + -K + ATPase subunits has been reported in the cardiac muscle membranes of diabetic animals [29], although a change in expression does not seem to occur in the retina [16]. Nevertheless, it is established that the renin-angiotensin system (RAS) and, in particular, that angiotensin-II (AngII), can modulate Na + -K + ATPase activity [30].…”
Section: Discussionmentioning
confidence: 99%
“…lateral pressure) of the polyunsaturated fatty acyl phospholipids within the lipid bilayer (46). In other studies dietary modulation of the -6:-3 fatty acyl ratio in heart or brain phospholipids has also been reported to alter kinetic properties of the different Na,K-ATPase isoforms (47)(48)(49). Although it is quite possible that kinetic effects are mediated by changes in the physical environment of the Na,K-ATPase, as suggested in these papers, in an intact membrane or reconstituted proteoliposomes the exact mechanism of effects of phospholipids on activity is not easily defined.…”
Section: Two Sites For Phospholipids; Biochemical and Structural Data-mentioning
confidence: 94%
“…While mechanisms responsible for an impairment of Na,K-ATPase during hyperglycemia remain to be elucidated, it has been suggested that alterations in membrane fatty acid composition, particularly related to a deficiency in DHA, might explain the abnormal Na ϩ transport observed in these patients (138,139). Djemli-Shipkolye et al (140) have demonstrated that fish oil supplementation can modify the fatty acid composition of sciatic nerve membranes of diabetic rats by decreasing LA and preventing the decrease of arachidonic and oleic acid.…”
Section: Effects On Diabetes Complicationsmentioning
confidence: 99%